INTEGRASI METODE PADA PEMBELAJARAN TEMATIK IPS DAN PKN PADA MASA PANDEMI COVID-19 DI SDIT ALAM GARUT - Tetep Dr.; maharani purnamasari (Journal Civics and Social Studies, 2021)
The COVID-19 pandemic has had a significant impact on the world of education, especially learning at school, learning challenges and offline has become a relentless tug of war until now. The use of learning methods demands teacher creativity in current conditions, so the ability to integrate various learning methods must continue to be carried out. This study examines the integration of learning methods in Social Studies and Citizenship Education thematic learning carried out by classroom teachers at SDIT ALAM GARUT during the COVID-19 pandemic. This research was conducted using a descriptive approach where data collection was done by interview, observation and documentation. Interviews were conducted with teachers, students, and parents, observations with teachers, students, and parents, as well as observing several supporting documents. The results showed that there was an integrated use of methods in Social Studies and Citizenship Education thematic learning at SDIT Alam Garut, including: lectures via voicenotes, direct or limited demonstrations via video, giving through photos, written assignments given via WhatsApp or students or parents taking assignments at the school. schools, and practices that are videoed and sent via the WhatsApp application. The use of this integration of learning methods is solely to maintain the continuity of the learning process for students at SDIT Alam Garut during the Covid 19 Pandemic.